TEKNOLOGI PEMANFAATAN CAIRAN PULPA HASIL SAMPING PENGOLAHAN KAKAO DI DESA ANGKAH, KECAMATAN SELEMADEG BARAT, KABUPATEN TABANAN - G. P. Ganda Putra; N. M. Wartini; I.W.G.S. Yoga (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The objectives of Community Service in accordance problems partners is to: 1) be able to accommodate a watery sweating byproduct of fermentation of cocoa beans that are not scattered in the processing site, 2) the determination of the purchase price of raw materials (pods of cocoa or cocoa beans wet), 3) complementary device administration, and 4) obtain product of cocoa vinegar that meets the requirements of SNI and ready for the market. Methods of activities that have been agreed, as follows: 1) engineering equipment/container fermentation of cocoa beans, 2) simple value chain analysis, 3) creation of administrative tools, such as: administrative activity, financial administration and the administrative requirements of the other, and 4) the process production and packaging of cocoa vinegar. The results of the activities are: 1) engineering fermentation container is done by adding a plastic tarp in the bottom of the container fermentation, a byproduct obtained watery sweating as much as 660 liters per month or 4620-5940 liters per year, 2) the determination of the purchase price for raw materials pods and/or wet cocoa beans on a profit margin of 20%, 25%, 30% respectively with a conversion of 0.0233; 0.0224; 0.0216 and /or 0.233; 0.224; 0.216 of the price of cocoa beans in the market, 3) administrative tools that have been made, including: administrative activities, financial administration and other administrative completeness devices, and 4) have been able to do the production process to produce cocoa vinegar products in packaging and introduced through expo- exhibitions and marketed to traditional markets and to the needs of their own members.